Liberal Internationalism: Theory, History, Practice - Stuenkel, Oliver (Meridiano 47 - Journal of Global Studies, 2017)
While liberalism keeps adapting to circumstances, its underlying dynamic is the same: Liberalism, Jahn, argues, is a political project that aims to establish individual freedom through private property and to protect and extend this freedom through government by consent - yet, it pursues this goal through the privatization and expropriation of common property and hence requires the production and reproduction of unequal power relations domestically and internationally. Liberalism is thus, in essence, made viable through power politics, with the mere difference that is uses liberal rhetoric as a fig leaf to conceal the ultimate goal: To provide a justification for American hegemony.